EFEKTIVITAS VIDEO TUTORIAL CAMTASIA STUDIO TERHADAP KEMANDIRIAN BELAJAR MAHASISWA PADA MATA KULIAH KOMPUTER AKUNTANSI (Studi Kasus pada Program Studi Akuntansi Universitas NU Sidoarjo) - Mohammad Taufiq (Universitas Nahdlatul Ulama Sidoarjo, 2020)
This study aims to determine the effectiveness of the application of Camtasia Studio video tutorials in increasing the independence of accounting students in accounting at the Nahdlatul Ulama University in Sidoarjo (Unusida) who take accounting computer courses. This research design is experimental research. This study includes sample research with sampling with purposive sampling, with certain considerations determining two classes that are conducting computer accounting lectures, namely Morning-Class and Afternoon-Class of 2018 Accounting Study Program as the Experimental and Control-Class. Data collected by the questionnaire and documentation method. To obtain a research instrument in the form of a questionnaire, a research trial was conducted on the Class-Morning class of 2017 then the results were tested for validity and reliability. A valid and reliable questionnaire is then used to collect research data on student learning independence. While the documentation method is used to know the general description of the population to be studied. Before the data analysis is performed first, the analysis prerequisites are tested which includes normality and homogeneity tests. The data analysis method used is the T-Test of separated variance type to determine changes in the level of student learning independence. The results of the study show that: (1) there is a difference in the learning independence of students after participating in learning using the Camtasia Studio video tutorial indicated by the average value of the control group during the initial independence test (Pre-Test) of 79.529 while the average when the final independence test (Post-Test) was 79,113 it shows the average difference of 0.415. (2) there is a difference in student learning independence after following the Camtasia Studio video tutorial learning which is indicated by the average value of the experimental group during the initial independence test (Pre-Test) of 84,150 while the average during the final independence test (Post-Test) of 80,050 shows that there is the average difference of 4,100. (3) there was an increase in student learning independence after following the Camtasia Studio video tutorial learning as indicated by the results of the separated variance t-test obtained by the P-Value of 0,000 which was smaller than 0.05 (α) while the Thitung result of 3.793 was greater than Table of 2.086 at a significance level of 5% (0.05). This means that based on the results of the T-Test and the mean score it can be concluded that the application of Camtasia Studio video tutorial learning is more effective in accounting computer learning compared to learning that does not use Camtasia Studio video tutorials